CHARACTERISTICS OF OPEN INNOVATION AND THEIR ADVICE TO THE DEVELOPMENT OF SMALL AND MEDIUM BUSINESS - Jovović, David (Poslovna ekonomija, 2018)
In contemporary business conditions, knowledge is a key economic category, especially due to significance of its commercialisation in innovations. It is increasingly more obvious that differences in the achieved level of innovativeness considerably determine developmental possibilities of an enterprise and economy as a whole. ‘Innovate or disappear’, became the credo of business policy of an enterprise in the last decade of the twentieth century. Bearing in mind the fact that since then small and medium-sized enterprises have increasingly become the drivers of increase of national production and overall employment, it is clear that the necessity for improvement of their innovativeness has reached its full expression in this period. This resulted from the simple fact that innovative small and medium-sized enterprises considerably contribute to overcoming of technological gaps of national economies, i.e. contribute to their transition from lower to higher level of technological development. The paper indicates the significance of open innovation concept for the improvement of innovativeness of small and medium-sized enterprises. By providing the process of intensive exchange of knowledge, means and technologies between certain economic subjects, the concept of open innovations contributes to improvement of innovativeness in the sector of small and medium-sized enterprises as a key driver of their competitiveness in the economy of knowledge. Innovations are a powerful means for new small and medium-sized enterprises to successfully enter the market and change the current situation, thus simultaneously enabling the existing enterprises to maintain or improve their position on the market by improvement of competitiveness. Innovative small and medium-sized enterprises participate in fluctuation of knowledge within innovation systems less as passive users, but more as a significant source of knowledge.